Chanticleer and the fox (New York : HarperCollins Publishers, 1986)
A rooster named Chanticleer, his voice was merrier than the merry organ that plays in church, and his crowing from his resting place was more trustworthy than a clock.
Adapted from Geoffrey Chaucer's Canterbury Tales. Winner of the Caldecott Medal.
Keywords: Rooster--Fiction; Children stories